In Search of Equality / Same-Sex Marriage and Psychology - Sutton Jon; The British Psychological Society (2005)
How Voters Decide, Childhood Obesity, Vanuatu, Couch Kids - Myth or Reality?, Fed Up and Friendless?, Serving up Trouble? Advertising Food to Children, Psychology in Vanuatu.